Barriers to education: Policies and perceptions of individuals with histories of sexual offenses in higher education. Issue 8 (17th November 2019) - Rubenstein, Lauren; Tabaczyk, Olivia M.; Jeglic, Elizabeth
Abstract: While education has been demonstrated to promote desistance, a person with a sex offense conviction faces numerous obstacles when pursuing a postsecondary education. In the present study, we investigated perceptions of university administrators toward applicants convicted of sexual offenses. Responses were collected through an online survey disseminated to national higher education administrator organizations. This is the first study to explore administrative perceptions of policies regarding applicants with a history of sexual offending and provides data on the restrictions faced by people with a sex offense conviction when applying to and attending institutes of higher education.